Programação para administração de redes de computadores: uma proposta de ensino-aprendizagem baseada no modelo de Sala de Aula Invertida - Oliveira, Silmar Antonio Buchner de (2018)
The initial disciplines of computer networks are, in general, taught in an essentially theoretical way and with little association with practice. Therefore, our research has resulted in a teaching-learning proposal in which, in addition to the theoretical part, there is a greater practical orientation for the student to be able to develop skills to solve day-by-day problems in Computer Networks using Programming resourses. We elaborated this proposal following the fundamentals of Constructive Alignment to develop teaching, learning and evaluation activities. We also adopt the invertted classroom hybrid teaching model, in which the student has access to the content previously, with the help of videos, links, tutorials, etc., and uses classroom time with the teacher, to solve practical problems on daily life of a professional of Computer Networks, using the Python language in a simulated network, in a Virtual Laboratory. We evaluated our teaching-learning proposal through a case study carried out with students of undergraduate courses in the area of computation of Porto Velho/RO city. In this study, we evaluated the performance of students with respect to the development of three skills in the field of Computer Networks: Identification of problems; Automation of solutions to problems; Association of solutions found with other possible problems. The results of this study evidenced students' progress on the three skills in solving problems involving network equipment and user actions monitoring, log analysis, remote backups, data synchronization and automatic issuance of alert messages. As a product of this research, we organized a Didactic Guide to Programming for Computer Network Administration containing all the teaching-learning material and dynamics used to assist in the application of the proposal by other teachers of Computer Networks.